Nuclear imaging in the field of dentistry: A review - Ahmad Buch, Sajad; G Babu, Subhas; Lorina Castelino, Renita; Rao, Shruthi; Madiyal, Ananya; Bhat, Supriya (Annals of Medical Research, 2021)
None
Keywords: Nuclear Medicine; Positron emission tomography(PET); Single photon emission computed tomography (SPECT); Fusion imaging i.